Avaliação da qualidade do serviço odontológico do Sistema Único de Saúde - SUS pelo usuário - Rós, Denise de Toledo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Understanding the aspects that involve the satisfaction of users of health services allows a broader and more accurate assessment of its evaluation, becoming the main benefit for the organization and planning of the service. In particular in dental sector the practice of user-centered evaluation has not been realized as yet a reality in many services. In this sense, the objective of this study was to analyze the satisfaction, resolubility and user's knowledge regarding the oral health services provided in SUS in the city of Araçatuba-SP. It is a cross-sectional survey, survey type, whose study population was consisted of dental users of SUS service (n = 461), including those who were under treatment and, preferably, those who have completed the service user experience dental. The technique used for data collection was standardized interpersonal interview in the waiting room of the Health Units, using an adapted form of the National Program Evaluation Health Service (PNASS) and Access and Quality Improvement Program (PMAQ ). For processing the data we used the statistical software Epi Info version 7.1.4. The sample consisted of 70.5% of female users, 57.0% single, earning 1-2 minimum wages (49.2%), and incomplete secondary education (39.3%). The main reason for the demand for the service was the dental treatment (50.7%). Of the total respondents, 75.3% said they had all their oral health problems resolved at the Health Unit and 76.2% were satisfied with the service provided. Among the respondents, 76.4% did not know where to complain, unknown the ombudsman system SUS, and among users who have some kind of complaint or suggestion service, 42.8% had some return. The satisfaction was associated with the perception of the resolubility of service (p <0.0001) and low income (p <0.0002). Low-income...

O entendimento das vertentes que envolvem a satisfação dos usuários dos serviços de saúde permite uma avaliação mais ampla e fiel do seu funcionamento, constituindo-se no principal subsídio para a organização e planejamento do serviço. Em especial, no setor odontológico a prática da avaliação centrada no usuário não tem se concretizado como uma realidade ainda em muitos serviços. Neste sentido, o objetivo deste trabalho foi analisar a satisfação, resolubilidade e o conhecimento do usuário com relação ao serviço de saúde bucal prestado na rede pública de saúde do SUS, no município de Araçatuba-SP. Trata-se de uma pesquisa transversal, tipo inquérito, cuja população de estudo foi composta por usuários do serviço odontológico do SUS (n=461), incluindo aqueles que estavam sob tratamento e, preferencialmente, aqueles que já concluíram a experiência de utilização do serviço odontológico. A técnica utilizada para coleta dos dados foi a entrevista interpessoal padronizada, na sala de espera das Unidades de Saúde, empregando-se um formulário adaptado do Programa Nacional de Avaliação do Serviço de Saúde (PNASS) e Programa de Melhoria do Acesso e Qualidade (PMAQ). Para o processamento dos dados foi utilizado o programa estatístico Epi Info, versão 7.1.4. A amostra foi composta por 70,5% de usuários do gênero feminino, 57,1% solteiros, com renda de 1 a 2 salários mínimos (49,2%), e ensino médio incompleto (39,3%). O principal motivo para a procura do serviço foi o tratamento odontológico (50,7%). Do total de entrevistados, 75,3% afirmaram ter todos os seus problemas de saúde bucal resolvidos na Unidade de Saúde e 76,2% estavam satisfeitos com o serviço prestado. Dentre os entrevistados, 76,4% não sabiam onde reclamar, desconhecendo o sistema de ouvidoria do SUS, e dentre os usuários que fizeram algum tipo...
Keywords: Sistema Único de Saúde (Brasil); Atenção primária à saúde; Saúde bucal; Satisfação do paciente; Assistência odontológica; Primary health care